Divided dose intramuscular regimen and single dose subcutaneous regimen for chloroquine: plasma concentrations and toxicity in patients with malaria. Issue 6538 (5th July 1986) - Phillips, R E; Warrell, D A; Edwards, G; Galagedera, Y; Theakston, R D; Abeysekera, D T; Dissanayaka, P
Abstract : Adults with malaria in Sri Lanka were treated with parenteral chloroquine diphosphate, either 2.5 mg base/kg intramuscularly at 0, 1, 12, 13, 24, and 25 hours or 5 mg base/kg subcutaneously at 0, 12, and 24 hours. Both regimens were completed with oral chloroquine phosphate, 5 mg base/kg, at 36 and 48 hours. Mean peak chloroquine concentrations in the first 12 hours, which were 0.5 (range 0.3-0.6) mg/l (1.4 (0.9-1.7) mu mol/l) [corrected] with the intramuscular regimen and 0.3 (0.2-0.4) mg/l (1.0 (0.7-1.3) mu mol/l) [corrected] with the subcutaneous regimen (p less than 0.05), were reached in median times of 90 (65-90) minutes and 30 (30-60) minutes respectively (p less than 0.05) after the start of treatment. The mean area under the plasma concentration curve for the first 12 hours was 1.4 (0.9-2.1) mg/l.h (4.5 (2.8-6.4) mu mol/l.h) [corrected] after intramuscular administration and 1.8 (0.8-2.3) mg/l.h (5.7 (2.7-7.2) mu mol/l.h) [corrected] after subcutaneous administration (p greater than 0.1). Mean maximum plasma concentrations were higher after intramuscular administration (0.6 (0.4-0.8) mg/l (1.7 (1.3-2.5) mu mol/l)) [corrected] than after subcutaneous administration (0.4 (0.4-0.5) mg/l (1.3 (1.3-1.5) mu mol/l)) [corrected] (p less than 0.05), but both regimens produced satisfactory plasma profiles. Chloroquine resistance was found in the only case of Plasmodium falciparum malaria. Chloroquine is absorbed rapidly after divided dose intramuscular injection and single dose subcutaneous injection and does not cause hypotension or neurotoxicity in adults. Similar regimens should be evaluated in children before the parenteral use of this drug is abandoned.